DAOMod: A Modeling Method for Decentralized Autonomous Organization Development - Avanzo, Sowelu; Pautasso, Daniele; Domenicale, Irene; Norta, Alex; Schifanella, Claudio; Hattingh, Marie; Mitwalli, Daniel Sami (Electronic Communications of the EASST, 2025)
Decentralized Autonomous Organizations (DAOs) are a type of Decentralized Applications (DApps) that utilize smart contracts to support governance processes. To achieve a high degree of utility of the system, stakeholders need to identify a suitable organizational structure in the early stages of design. While Model-Driven Development (MDD) methods are established for DApp and smart contract design, they lack specialization for modeling the organizational structures of DAOs. To address this gap, we propose a modeling language and a method which support crucial DAO design and development phases. The method is evaluated through an in vivo case study. Unlike existing solutions, comprehensive stepwise guidance is provided by our method for both technical and non-technical stakeholders involved in DAO development from the initial stages of the project.